Determining Changes in Mangrove Cover Using Remote Sensing with Landsat Images: a Review (2023)
Mangroves are ecosystems within the intertidal zone of tropical and subtropical coasts; they offer ecosystem services such as protection from coastal erosion and storms and flood control, act as carbon sinks and are also sources of income by providing various forest products. However, their cover is rapidly disappearing worldwide, which makes the diagnosis and monitoring of the state of these important ecosystems, as well as their restoration and conservation, a challenge. Remote sensing is a promising technique that provides accurate and efficient results in the mapping and monitoring of these ecosystems. The Landsat sensor provides the most used medium-resolution images for this type of study. The main objective of this article is to provide an updated review of the main remote sensing techniques, specifically Landsat satellite imagery, used in the detection of changes and mapping of mangrove forests, as well as a review of climatic and/or chemical factors related to changes in the spatial distribution of these ecosystems.